Exploring Ethnoscience-Based Physics Concepts in the Pottery-Making Process of Kasongan Jogja: A Study on Heat and Temperature - Liwun, Natalia Lena; Huda, Choirul; Sayyadi, Muhammad (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This research explores the identification of physics concepts, particularly heat and temperature, within the traditional process of pottery-making. The stages of pottery production naturally involve thermal processes such as heat transfer and temperature variations. Employing a qualitative descriptive method with an ethnoscientific (cultural study) approach, this study involved two participants a man and a woman who are pottery artisans in Kasongan, Bantul, Yogyakarta. Data were collected through interviews, direct observations, and documentation. The findings show that the drying and firing phases in pottery production clearly demonstrate the application of heat and temperature principles. The ethnoscience approach proves to be an effective bridge between scientific knowledge and local cultural practices, enhancing students’ appreciation of both science and cultural heritage. This study contributes positively to the integration of ethnoscience in physics education by connecting classroom learning to real-life practices. Future research is expected to further strengthen the link between science and culture and examine the role of technology in modern pottery without compromising its cultural essence.